Cohort study of depressed mood during pregnancy and after childbirth - Evans, Jonathan (BMJ, 2001)
OBJECTIVE: To follow mothers' mood through pregnancy and after childbirth and compare reported symptoms of depression at each stage. DESIGN: Longitudinal cohort study. SETTING: Avon. PARTICIPANTS: Pregnant women resident within Avon with an expected date of delivery between 1 April 1991 and 31 December 1992. MAIN OUTCOME MEASURES: Symptom scores from the Edinburgh postnatal depression scale at 18 and 32 weeks of pregnancy and 8 weeks and 8 months postpartum. Proportion of women above a threshold indicating probable depressive disorder. RESULTS: Depression scores were higher at 32 weeks of pregnancy than 8 weeks postpartum (difference in means 0.88, 95% confidence interval 0.79 to 0.97). There was no difference in the distribution of total scores or scores for individual items at the four time points. 1222 (13.5%) women scored above threshold for probable depression at 32 weeks of pregnancy, 821 (9.1%) at 8 weeks postpartum, and 147 (1.6%) throughout. More mothers moved above the threshold for depression between 18 weeks and 32 weeks of pregnancy than between 32 weeks of pregnancy and 8 weeks postpartum. CONCLUSIONS: Symptoms of depression are not more common or severe after childbirth than during pregnancy. Research and clinical efforts need to be moved towards understanding, recognising, and treating antenatal depression.